Virtual History: How Videogames Portray the Past - Wainwright, A. Martin (Routledge, 2019)
Virtual History examines many of the most popular historical video games released over the last decade and explores their portrayal of history. The book looks at the motives and perspectives of game designers and marketers, as well as the societal expectations addressed, through contingency and determinism, economics, the environment, culture, ethnicity, gender, and violence. Approaching videogames as a compelling art form that can simultaneously inform and mislead, the book considers the historical accuracy of videogames, while also exploring how they depict the underlying processes of history and highlighting their strengths as tools for understanding history. The first survey of the historical content and approach of popular videogames designed with students in mind, it argues that games can depict history and engage players with it in a useful way, encouraging the reader to consider the games they play from a different perspective. Supported by examples and screenshots that contextualize the discussion, Virtual History is a useful resource for students of media and world history as well as those focusing on the portrayal of history through the medium of videogames.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé